Revisão taxonômica de Myleus Müller & Troschel, 1844 e Myloplus Gill, 1896 (Characiformes, Serrasalmidae). - Gomes, Vivian Nunes (2015)
Members of Characiformes present varied morphologic and ecologic standards, inhabiting continental waters of Africa, South and Central America and Southern North America, with highest diversity in Neotropical region. It is composed by 18 families, with about 270 genera and more than 1,600 species. Systematics and taxonomy of Characiformes are poorly solved, mainly for some families such as Serrasalmidae. This family has been considered as either family or subfamily by several authors since its establishment in middle 18th century. Currently, the family status is most accepted. Serrasalmidae is represented by almost 90 species distributed in 17 genera in the Neotropical region, occurring in floodplains, lakes, flooded forests, rapids and headwaters. They can be recognized by having laterally compressed body, a series of ventral abdominal spines, dorsal fin with more than 16 rays and usually an anteriorly forwarded pre-dorsal spine. Besides similar body features, they can be differentiated by the arrangement and shape of teeth. Myleus and Myloplus, known as ?pacus?, are the most speciose genera within Serrasalmidae, currently represented by 13 valid species. However, allocating species to one or other genus is one of the biggest issues for the group. Therefore, the main scope of this work is to define and allow recognition of Myleus and Myloplus, besides recognizing all the valid species of each genus. After examining exhaustive material and literature regarding all nominal species of both genera, we conclude that they can be diagnosed mainly for Myloplus having the series of premaxillary teeth separated from each other, whereas Myleus has those series juxtaposed. We recognized two valid species in Myleus, Myleus knerii e Myleus setiger and M. arnoldi, M. asterias, M. levis, M. lobatus, M. planquettei, M. rhomboidalis, M. rubripinnis, M. schomburgkii, M. ternetzi M. tiete and M. torquatus in Myloplus. Synonymies, diagnoses, pictures, geographic distribution and comments for all valid species are given. An identification key for all species is also provided.